THE EFFECT OF CAPITAL STRUCTURE ON THE SHARE PRICE OF COAL SUB-SECTOR COMPANIES WITH BUSINESS DIVERSIFICATION AS A CODING VARIABLE - Suryana, Teddy; Yonathan, Randy; Meliala, Yefta Trifosa (Sean Institute, 2022)
This study aims to analyze the role of business diversification in moderating the influence of capital structure on the share price of coal sub-sector companies on the Indonesia Stock Exchange for the 2017-2021 period. The study used causality design with a quantitative approach to test hypotheses statistically. Sample determination was carried out using purposive sampling techniques so that 21 companies were obtained. Data analysis was carried out with moderation regression analysis with the help of the SPSS version 26 program. The results of data analysis show that the capital structure has a negative and significant effect on stock prices, business diversification has a positive and significant effect on the company's stock price, business diversification can moderate the influence of capital structure on the share price of coal sub-sector companies on the Indonesia Stock Exchange for the period 2017 - 2021.